THE ROLE OF THE CATHOLIC CHURCH IN THE SUBJECTION OF THE PEOPLES OF PRE-COLUMBIAN LATIN AMERICA - Карташов, Микита; Сапицька, Олена (SWorldJournal, 2024)
The article highlights the thesis that on the example of the conquest of the peoples of pre-Columbian Latin America by Europeans, it is possible to trace the positive and negative factors of colonial policy, as well as to demonstrate that the excessive in